'The Dispositive': Foucault's Concept for Organizational Analysis?. Issue 3 (March 2021) - Villadsen, Kaspar
Foucault's notion 'the dispositive' has been introduced in organization studies as a highly promising concept. However, its analytical and empirical potentials remain to be fully explored. This article develops dispositional analytics which conceives of organizations as pervaded by multiple dispositives that interact, reinforce or contradict one another. In this reconstruction, particular emphasis is given to the visibility produced by dispositives, through which subjects and object emerge in a particular prescriptive light. Furthermore, analytical privilege is given to relations over substance. This means foregrounding the interrelations between dispositives as well as the dispositive's 'internal relationality', that is, the relations established by each dispositive out of which organizational problems arise and transform. The framework's potentials are explored in a study of care workers' responses to a management reform that disciplined and depersonalized care-giving. The difficulties that care workers faced in straddling legal demands, service standardization and care ethics are understood as a situation of heterogeneous dispositions. In this context, care workers and their managers tactically reconstructed their subjectivities, relating to the dispositives in diverse and unexpected ways.